PREVALENCE OF VIRULENCE FACTORS AMONG CLINICAL ISOLATES OF ENTEROCOCCUS SPP. - L, Ravichandran; S, Umadevi; S, Pramodhini; S, Srirangaraj; Ks, Seetha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To identify some of the virulence factors such as hemolysin, gelatinase, and biofilm production among the clinical isolates of enterococci. Methods: Hemolysin detection using sheep blood agar. Gelatine agar was used for gelatinase production, and tube adherence method was used for detecting biofilm production. Results: Hemolysin production observed in 49% of isolates, gelatinase production in 41% of isolates, and 46% of isolates were produced biofilm. Conclusion: Virulence factors production was noticed more in Enterococcus faecalis than Enterococcus faecium. It is necessary to find the production of important virulence factors among the clinical isolates as they are always associated with virulence of the organism including drug resistance. Keywords: Hemolysin, Gelatinase, Biofilm, Enterococcus.